Pengaruh Kualitas Pelayanan dan Sikap Penyidik terhadap Kepuasan Publik dengan Kepercayaan sebagai Variabel Intervening di Polres Nunukan - Ratijun M. Lubis; Dwi Putranto Riau; Didik G. Suharto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of service quality and investigator attitudes on public satisfaction, with public trust as an intervening variable in the Criminal Investigation Directorate of the Nunukan Police. The research method used a quantitative approach with an explanatory survey design. The study population consisted of 390 public complaint reports from 2024 to April 2025, with a sample of 197 respondents determined using the Slovin formula and proportional random sampling technique from six police stations. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression, hypothesis testing (t-test and F-test), and the Variance Accounted For (VAF) mediation test. The results showed that service quality had a positive and significant effect on public trust and satisfaction. Service attitude did not have a significant effect on public trust, but a positive and significant effect on public satisfaction. Public trust had a negative and significant effect on public satisfaction. Furthermore, public trust did not mediate the effect of service quality on public satisfaction, but partially mediated the effect of service attitude on public satisfaction. The study's conclusions indicate that in the context of border areas, the quality of technical services is a key factor in building public satisfaction, while high levels of public trust can lead to excessive expectations, potentially lowering public satisfaction with police services.